Stitching freedom : embroidery & incarceration - Rosner, Isabella (s.l. : Common Threads Press, 2024)
"For centuries, people have stitched in good times and in bad, finding strength in the needle moving in and out of fabric. Stitching Freedom explores the embroidery made in prisons and mental health hospitals - those who have embroidered to distract, to reflect or to calm. From Mary, Queen of Scots to Lorina Bulwer, embroidery historian and curator Isabella Rosner unpicks twelve embroidered histories to discover what can be created when freedom is out of reach."--
Introduction -- Virtue flourishes by wounding -- In lonely grief I sigh -- Damnation hell tramp den of old women -- I plunge headlong into disaster -- Bold bad ones -- Filled with my love always -- Fuck Hitler -- Codemakers, codebreakers -- Many innocents have perished -- Becoming God -- The mystery of Myrllen -- Betsy Ross -- Conclusion.
boek
Keywords: Copeland, Takako